Structural requirements for parathyroid hormone action in mature bone. Effects on release of cyclic adenosine monophosphate and bone gamma-carboxyglutamic acid-containing protein from perfused rat hindquarters. - Calvo, M S (1985)
To determine the structural requirements for parathyroid hormone (PTH) activity in mature bone, we perfused the surgically isolated hindquarters of adult male rats with either native bovine PTH-(1-84) [bPTH-(1-84)] or the synthetic amino-terminal fragment, bovine PTH-(1-34) [bPTH-(1-34)]. Changes in the release of cyclic AMP (cAMP) and bone Gla protein (BGP) were monitored as evidence of bone-specific response to PTH; tissue specificity of the cAMP response was confirmed through in vitro examination on nonskeletal tissue response to PTH. Biologically active, monoiodinated 125I-bPTH-(1-84) was administered to determine if mature murine bone cleaves native hormone. We found that perfused rat bone continuously releases BGP, and that both bPTH-(1-84) and bPTH-(1-34) acutely suppress this release. In addition, both hormones stimulate cAMP release from perfused rat hindquarters. When examined on a molar basis, the magnitude of the cAMP response was dose-dependent and similar for both hormones, with doses yielding half-maximal cAMP responses. The response for bPTH-(1-34) was 0.5 nmol and for bPTH-(1-84) was 0.7 nmol. Moreover, biologically active 125I-bPTH-(1-84) was not metabolized in our hindquarter perfusion system. These findings indicate that PTH-(1-84) does not require extraskeletal or skeletal cleavage to an amino-terminal fragment in order to stimulate cAMP generation in, or suppress BGP release from, mature rat bone.